Synthesis and antiproliferative activities of novel quartenary ammonium spinosyn derivatives. Issue 20 (1st November 2018) - Ma, Da-You; Wang, Long-Long; Lai, Qin; Peng, Kun-Jian; Li, Xuan; Li, Zeng-Xia; Liu, Li-Jun; Luo, Zhi-Yong; Liu, Su-You
Graphical abstract: Highlights: Thirteen novel quartenary ammonium spinosyn derivatives were synthesized. Greatly enhanced antiproliferative activities. Lipophicility has a great influence on the antiproliferative effects of these derivatives. Compound11d exhibited remarkably enhanced OXPHS inhibition and apoptosis inducing ability. Abstract: In order to enhance the mitochondria-targeting ability of spinosad. A series of quartenary ammonium spinosyn derivatives was designed and synthesized. Some of the derivatives displayed greatly enhanced antiproliferative ability towards tested human cancer cell lines. The structure activity relationship study indicated that lipophilicity has a great influence on the antiproliferative effects of these derivatives. The most active compound11d exhibited remarkably enhanced OXPHS inhibition and apoptosis inducing ability than spinosyn A.